ANALISIS TITIK-TITIK KRITIS KETERTELUSURAN PADA RANTAI PASOK KAKAO ACEH - Yusriana,Yandra Arkeman, Sapta Raharja, Purwiyanto Haryadi (Department of Agroindustrial Technology, Bogor Agricultural University, 2016)
Traceability system for Aceh cocoa supply chain is identification of the documents which includies the product specification information, production process, actors and location as well as the production management. The objectives of this research were to determine critical points and its impacts on traceability system which was developed. Fuzzy-failure mode effect and critically analysis (F-FMECA) technique were used to determine the critical points. Data inputs came from expert’s panel (academicians, researcher and practitioners) with Ph.D for academician and researcher, and 15 years experiences for business man. The results of the study showed that there were several critical points on all actors in Aceh cocoa supply chain. Critical points on all actors include all the points that have a value of risk priority number (RPN) ranking high category.Keywords: Aceh cocoa, F-FMECA , supply chain, traceability system